A perfusion resin grafted with sodium citrate and its preparation process
By forming a composite hydrogel coating with sodium citrate graft on the resin material, the problem that blood perfusion resin material can easily lead to coagulation and non-specific protein adsorption is solved, and its adsorption ability to blood toxins and anticoagulation is improved. Performance, achieving more efficient blood purification.
Patent Information
- Application Number
- CN202410256137.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-03-06
AI Technical Summary
Existing blood perfusion resin materials are prone to coagulation when they come into contact with blood, and there are non-specific protein adsorption problems, which affects its purification effect.
Compound hydrogels are prepared by reaction of glycidyl methacrylic acid and chitosan, and grafting is carried out by sodium citrate to form a coating embedded on the resin microparticles, thereby enhancing the adsorption ability of the adsorption material and Anticoagulant activity, reduces the concentration of calcium ions in the blood to inhibit coagulation.
It significantly improves the adsorption ability and anticoagulation performance of resin materials on blood toxins, reduces the possibility of coagulation during blood perfusion, and enhances the blood purification effect.
Smart Images

Figure BDA0004729303620000071 
Figure BDA0004729303620000073 
Figure BDA0004729303620000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of perfusion resins, and in particular to a perfusion resin grafted with sodium citrate and a preparation process thereof. Background Art
[0002] Blood purification refers to a therapy in which the patient's blood is purified by an extracorporeal membrane / adsorbent purification device and then returned to the body. It can replace the patient's own detoxification system to remove toxins and has saved the lives of many patients with different diseases, such as poisoning, uremia, liver disease, hyperlipidemia, sepsis, autoimmune diseases, etc. According to different purification principles, blood purification can be divided into hemodialysis, hemofiltration, plasma exchange and hemoperfusion. Among them, hemoperfusion therapy is also called blood purification adsorption therapy, which is based on the principle of "adsorption" and uses adsorbents to remove toxins from the blood. The core of hemoperfusion therapy is hemoperfusion adsorbent material.
[0003] Since the adsorption material needs to be in direct contact with the blood during blood perfusion, when the material comes into contact with the blood as a foreign body, coagulation usually occurs on the surface of the material within 1-2 minutes, and the occurrence of coagulation is also related to multiple components in the blood, such as plasma proteins, coagulation factors, red blood cells and platelets. There are two main pathways for coagulation formation: first, the activation of coagulation factors leads to the formation of fibrin gel; second, the adhesion, release and aggregation of platelets promote the formation of platelet thrombus. However, the formation of these two processes is derived from the induction of the plasma protein layer adsorbed on the surface of the material.
[0004] Therefore, in order to reduce the impact on the blood, the blood perfusion adsorbent material must not only have good adsorption performance, but also good blood compatibility. In the field of blood perfusion, the most common polymer material is resin, which is also a type of blood perfusion adsorbent material with an early origin and currently widely used in clinical practice. Resin is a synthetic porous polymer material, including anion / cation exchange resins with positive / negative charges and neutral adsorption resins without charge. At present, resin perfusion materials generally include polystyrene resins, acrylic resins, etc., but the current resin perfusion materials still face the problem of nonspecific protein adsorption, which can easily cause coagulation during blood perfusion. Summary of the invention
[0005] In order to reduce the possibility of coagulation during blood perfusion therapy, the present application provides a perfusion resin grafted with sodium citrate and a preparation process thereof.
[0006] In the first aspect, the present application provides a preparation process of a perfusion resin grafted with sodium citrate using the following technical solution:
[0007] A preparation process of a perfusion resin grafted with sodium citrate comprises the following steps:
[0008] The glycidyl methacrylate dextran and chitosan are reacted to obtain a glycidyl methacrylate dextran / chitosan composite solution, and then a composite hydrogel is obtained after cooling by injection molding;
[0009] Then, the composite hydrogel is grafted with sodium citrate to obtain a composite hydrogel grafted with sodium citrate, and finally, the composite hydrogel grafted with sodium citrate is used to embed resin microparticles to obtain a perfusion resin.
[0010] By adopting the above technical solution, glycidyl methacrylate dextran is obtained by chemically modifying dextran with glycidyl methacrylate. Since the coating formed by dextran hydrogel on the surface of resin microparticles can enhance the adsorption capacity of the adsorbent material for heterotropic proteins, dextran is prone to block the adsorption pores of resin microparticles, thereby hindering the adsorption of toxins in the blood. By using glycidyl methacrylate dextran as the coating material, after chemically modifying dextran with glycidyl methacrylate, the integrity of the dextran hydrogel can be made higher, and it is not easy to block the adsorption pores of resin microparticles, and the dextran hydrogel coating can have a richer network structure and a higher water content, so as to further enhance the anticoagulant activity of the adsorbent material.
[0011] The composite solution is prepared by reacting methacrylate glycidyl dextran and chitosan. Since chitosan contains a large number of amino groups on the molecular chain, it can undergo ionic crosslinking reaction with citrate ions under certain reaction conditions to form a gel, so as to achieve the grafting of citrate ions on the composite hydrogel, and further achieve the grafting of citrate ions on the surface of resin microparticles. In addition to coagulation caused by plasma protein adsorption, rapid coagulation can also be caused when there are more calcium ions in the blood environment as a coagulation factor. Since sodium citrate is an excellent chelating agent, it has the ability to chelate calcium ions in the blood environment, thereby reducing the amount of calcium ions in the blood during the blood perfusion process, thereby further reducing the possibility of coagulation during the blood perfusion process.
[0012] Optionally, the method for preparing the methacrylate glycidyl dextran / chitosan composite solution comprises the following steps: adding chitosan powder to a certain amount of acetic acid solution (volume fraction is 3-4%), stirring for 12-14 hours at room temperature, and obtaining a chitosan solution after complete dissolution;
[0013] Add methacrylate glycidyl dextran to the chitosan solution, stir for 12-14 hours under 50-55° C. water bath conditions, mix evenly and completely dissolve, then place in a 50-55° C. oven for 48-50 hours, remove bubbles, and obtain a methacrylate glycidyl dextran / chitosan composite solution, wherein the total concentration of methacrylate glycidyl dextran and chitosan is 20-25wt%.
[0014] By adopting the above technical scheme, since methacrylate glycidyl dextran has good biocompatibility, good temperature sensitivity and plasticity, the above method can make methacrylate glycidyl dextran and chitosan form a uniform composite solution, so as to facilitate the subsequent formation of a uniform and stable composite hydrogel, and make the grafting of sodium citrate on the composite hydrogel more uniform and comprehensive.
[0015] Optionally, in the above preparation process, the mass ratio of chitosan to glycidyl methacrylate dextran is 1:(3-10).
[0016] By adopting the above technical solution, the chitosan and methacrylate glycidyl dextran of the above quality can make the formed composite hydrogel more stable in properties.
[0017] Optionally, the process of grafting the composite hydrogel with the sodium citrate comprises the following steps:
[0018] The composite hydrogel is immersed in a sodium citrate solution as a whole, taken out after 12-14 hours, and then immersed and washed in deionized water for 2-3 days, with the water being changed every 8-10 hours, so that the hydrogel reaches a swelling equilibrium state and excess sodium citrate is removed, thereby obtaining a composite hydrogel grafted with sodium citrate.
[0019] By adopting the above technical scheme, in the acidic environment of sodium citrate solution, the amino groups on the chitosan molecular chains in the composite hydrogel are protonated and converted into positively charged ammonium ions, which can undergo ionic cross-linking reaction with multivalent anions, such as citrate ions, to form a gel, thereby achieving the grafting of sodium citrate onto the composite hydrogel.
[0020] Optionally, in the above preparation method, the concentration of the sodium citrate solution is 0.3-0.5 mol / L.
[0021] By adopting the above technical solution, the sodium citrate solution of the above concentration can make the pH of the solution environment of chitosan in the composite hydrogel better promote the protonation of amino groups to positively charged ammonium ions.
[0022] Optionally, the resin microparticles are at least one of polymethyl methacrylate resin and polystyrene resin.
[0023] By adopting the above technical scheme, the resin microparticles prepared by the above resin types all have a relatively developed mesoporous structure, and have stronger adsorption performance for toxins in the blood; and all have good chemical stability and mechanical strength, and can exist stably during the subsequent embedding treatment and perfusion process, and are not easy to cause biological contamination to the blood in the perfusion.
[0024] Optionally, the particle size of the resin microparticles is 0.01-0.1 mm.
[0025] By adopting the above technical solution, the adsorbent obtained after embedding the resin microparticles of the above particle size is of moderate size and can better contact with the perfused blood to enhance the effect of adsorption and purification of blood toxicity.
[0026] Optionally, the embedding process comprises the following steps:
[0027] The resin microparticles are weighed and poured into a composite hydrogel sol grafted with sodium citrate (concentration of 3-5wt%) and stirred evenly. The evenly mixed sol is dropped into a 2-5wt% CaCl2 solution to cross-link into spheres, and then the resin for perfusion is obtained after curing, washing and drying.
[0028] Optionally, the mass ratio of the resin microparticles to the composite hydrogel sol grafted with sodium citrate is 1:(5-7).
[0029] By adopting the above technical scheme, the above mass ratio of resin microparticles and composite hydrogel sol can make the coating thickness formed by the composite hydrogel grafted with sodium citrate on the surface of the resin microparticles moderate and form a sufficient grid size and permeability.
[0030] In the second aspect, the present application provides a perfusion resin grafted with sodium citrate using the following technical solution: a perfusion resin grafted with sodium citrate is prepared by the above-mentioned preparation process of the perfusion resin grafted with sodium citrate. In summary, the present application includes at least one of the following beneficial technical effects:
[0031] 1. Using glycidyl methacrylate dextran as the coating material, after chemical modification of dextran with glycidyl methacrylate, the dextran hydrogel can have a higher integrity, is less likely to block the adsorption pores of the resin microparticles, and can make the dextran hydrogel coating have a richer network structure and a higher water content, so as to further enhance the anticoagulant activity of the adsorption material;
[0032] 2. The composite solution is prepared by reacting methacrylate glycidyl dextran and chitosan. Since the chitosan molecular chain contains a large number of amino groups, it can undergo ionic cross-linking reaction with citrate ions under certain reaction conditions to form a gel, so as to achieve the grafting of citric acid ions on the composite hydrogel, and further achieve the grafting of citric acid ions on the surface of resin microparticles. Sodium citrate is an excellent chelating agent and has the ability to chelate calcium ions in the blood environment, thereby reducing the amount of calcium ions in the blood during the blood perfusion process, thereby further reducing the possibility of coagulation during the blood perfusion process. DETAILED DESCRIPTION
[0033] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0034] 1. Implementation
[0035] Embodiment 1:
[0036] A perfusion resin grafted with sodium citrate, the preparation method of which comprises the following steps:
[0037] 1) Preparation of Glycidyl Methacrylate Dextran / Chitosan Composite Solution
[0038] Add 10 g of chitosan powder to a certain amount of acetic acid solution (volume fraction 3.5%), stir for 13 h at room temperature, and obtain a chitosan solution after the chitosan powder is completely dissolved;
[0039] In the chitosan solution, 30 g of glycidyl methacrylate dextran was added, stirred for 13 h in a 50°C water bath, evenly mixed and completely dissolved, and then placed in a 50°C oven for 50 h to remove bubbles to obtain a glycidyl methacrylate dextran / chitosan composite solution (the mass ratio of chitosan and glycidyl methacrylate dextran was 1:3), wherein the total concentration of glycidyl methacrylate dextran and chitosan was 23 wt%.
[0040] The prepared methacrylate glycidyl dextran / chitosan composite solution was added to the mold while hot without generating bubbles, and then moved to a 4°C refrigerator and allowed to stand for 5 hours. The mold was removed to obtain the composite hydrogel.
[0041] 2) Grafting treatment:
[0042] A sodium citrate solution with a concentration of 0.4 mol / L was prepared by the neutralization reaction of citric acid and sodium hydroxide. The composite hydrogel was immersed in the sodium citrate solution prepared above, taken out after 13 hours, and then immersed and washed in deionized water for 3 days. The water was changed every 9 hours to allow the hydrogel to reach a swelling equilibrium state and remove excess sodium citrate, thereby obtaining a composite hydrogel grafted with sodium citrate.
[0043] 3) Embedding treatment
[0044] The composite hydrogel grafted with sodium citrate prepared above was prepared into a sol with a concentration of 4wt%, 20g of resin microparticles were weighed and poured into 120g of composite hydrogel sol grafted with sodium citrate and stirred evenly (the mass ratio of resin microparticles to composite hydrogel sol grafted with sodium citrate was 1:6), the evenly mixed sol was dripped into a 4wt% CaCl2 solution to cross-link into spheres, and cured at 4°C for 10h, washed with distilled water 5 times, and dried at 75°C to obtain a perfusion resin;
[0045] The resin microparticles are polystyrene resin purchased from Handan Congtai District Huangrun Chemical Co., Ltd., and the particle size of the polystyrene resin is 0.05 mm.
[0046] Embodiment 2:
[0047] A perfusion resin grafted with sodium citrate is different from Example 1 in that: in the process of preparing the methacrylate glycidyl dextran / chitosan composite solution, the mass ratio of chitosan to methacrylate glycidyl dextran is 1:7.
[0048] Embodiment 3:
[0049] A perfusion resin grafted with sodium citrate is different from Example 1 in that: in the process of preparing the methacrylate glycidyl dextran / chitosan composite solution, the mass ratio of chitosan to methacrylate glycidyl dextran is 1:10.
[0050] Embodiment 4:
[0051] A perfusion resin grafted with sodium citrate is different from Example 2 in that: in the methacrylate glycidyl dextran / chitosan composite solution, the total concentration of methacrylate glycidyl dextran and chitosan is 20wt%.
[0052] Embodiment 5:
[0053] A perfusion resin grafted with sodium citrate is different from Example 2 in that: in the methacrylate glycidyl dextran / chitosan composite solution, the total concentration of methacrylate glycidyl dextran and chitosan is 25wt%.
[0054] Embodiment 6:
[0055] A perfusion resin grafted with sodium citrate, which is different from Example 2 in that: during the grafting process, the concentration of the sodium citrate solution is 3 mol / L.
[0056] Embodiment 7:
[0057] A perfusion resin grafted with sodium citrate, which is different from Example 2 in that: during the grafting process, the concentration of the sodium citrate solution is 5 mol / L.
[0058] Embodiment 8:
[0059] A perfusion resin grafted with sodium citrate is different from Example 2 in that: during the grafting process, the composite hydrogel is immersed in a sodium citrate solution as a whole and taken out after 12 hours.
[0060] Embodiment 9:
[0061] A perfusion resin grafted with sodium citrate is different from Example 2 in that: during the grafting process, the composite hydrogel is immersed in a sodium citrate solution as a whole and taken out after 14 hours.
[0062] Embodiment 10:
[0063] A perfusion resin grafted with sodium citrate, which is different from Example 2 in that the particle size of the resin microparticles is 0.01 mm.
[0064] Embodiment 11:
[0065] A perfusion resin grafted with sodium citrate, which is different from Example 2 in that the particle size of the resin microparticles is 0.1 mm.
[0066] Embodiment 12:
[0067] A perfusion resin grafted with sodium citrate is different from Example 2 in that: during the embedding treatment, the mass ratio of the resin microparticles to the composite hydrogel sol grafted with sodium citrate is 1:5.
[0068] Embodiment 13:
[0069] A perfusion resin grafted with sodium citrate is different from Example 2 in that: during the embedding treatment, the mass ratio of the resin microparticles to the composite hydrogel sol grafted with sodium citrate is 1:7.
[0070] 2. Comparison
[0071] Comparative Example 1:
[0072] The difference from Example 2 is that methacrylate glycidyl dextran is directly used to prepare a solution with a concentration of 23%, and a hydrogel is obtained after injection molding and cooling, and then sodium citrate is used to graft the hydrogel.
[0073] Comparative Example 2:
[0074] The difference from Example 2 is that during the preparation of the composite solution, an equal amount of glycidyl methacrylate dextran is replaced by dextran.
[0075] Comparative Example 3:
[0076] The difference from Example 2 is that sodium citrate is not used to graft the composite hydrogel.
[0077] 3. Performance test
[0078] 1) Adsorption performance evaluation:
[0079] Take 15 ml of plasma solution of interleukin IL-6 and bilirubin respectively, add 2 ml of perfusion resin prepared in the above Examples 1-13 and Comparative Examples 1-3, shake at 37°C for 2 hours; and detect the concentration of each adsorbed substance in the original plasma and the plasma after adsorption by the adsorbent by a fully automatic biochemical analyzer. The adsorption rate (AP) is calculated by the following formula, and the calculation results are shown in Table 1.
[0080] Where C b and C a are the concentrations of each adsorbed substance in the original plasma and the plasma sample after adsorption by the adsorption material, respectively.
[0081] 2) Blood compatibility evaluation:
[0082] 1. Determination of plasma protein adsorption quantity:
[0083] The perfusion resins prepared in Examples 1-13 and Comparative Examples 1-3 were weighed and placed in test tubes, 2 mL of fresh plasma was added to each test tube, and the sealed test tubes were placed in a 37°C water bath for 60 min, then 50 μL of plasma was taken out from each test tube and placed in a new test tube, 2 mL of total protein test agent was added to each new test tube in turn, the sealed test tubes were placed in a 37°C water bath for 30 min, and the absorbance of the sample solution in each test tube was measured at a wavelength of 545 nm. The total protein concentration in each test tube solution was calculated according to the following formula:
[0084]
[0085] Where C T and C Sare the total protein concentration of the sample solution to be tested and the total protein concentration of the standard solution, respectively. T and A S are the absorbance of the sample solution to be tested and the absorbance of the standard solution, respectively, where C S 70g / L, A S is 0.500.
[0086] The total plasma protein adsorption was calculated according to the following formula. The calculation results are shown in Table 1.
[0087] Where AD represents the mass of total plasma protein adsorbed per mg of adsorbent material; C B and C A are the total protein concentration of PP nonwoven samples before and after adsorption (g / L), V is the added plasma volume (mL), and W is Sample is the weight of the adsorbent material to be tested (mg).
[0088] 2. Determination of platelet adhesion quantity:
[0089] The lactate dehydrogenase (LDH) method was used to measure the number of platelets adhered to the perfusion resin prepared in Example 1-13 and Comparative Example 1-3. The measurement results are shown in Table 1.
[0090] 3) Determination of plasma calcium concentration:
[0091] First, the plasma calcium concentration of fresh plasma was tested by arsenic azo III method, and the plasma calcium concentration in fresh plasma was 1.78mmol / L;
[0092] The perfusion resins prepared in Examples 1-13 and Comparative Examples 1-3 were weighed and placed in test tubes, 2 mL of fresh plasma was added to each test tube, the sealed test tubes were placed in a 37°C water bath and kept at a constant temperature for 60 min, and then 50 μL of plasma was taken out from each test tube, and the plasma calcium concentration was detected by the azo arsenic III method. The test results are shown in Table 1.
[0093] Table 1:
[0094]
[0095]
[0096] 4. Results Analysis and Summary
[0097] Combining Examples 1-3 and Table 1, it can be seen that in the process of preparing the methacrylate glycidyl dextran / chitosan composite solution in Examples 1-3, the mass ratios of chitosan and methacrylate glycidyl dextran are different. From Table 1, it can be seen that the adsorption rates of interleukin IL-6 and bilirubin in Example 2 are higher than those in Example 1 and Example 3, and the plasma protein adsorption amount, platelet adhesion number and plasma calcium concentration are lower than those in Example 1 and Example 3, which means that the adsorption capacity and anticoagulant ability of Example 2 for toxins in the blood are better than those in Example 1 and Example 3.
[0098] In addition, in Comparative Example 1, methacrylate glycidyl dextran was directly used to prepare a solution with a concentration of 23%, and a hydrogel was obtained after injection molding and cooling, and then the hydrogel was grafted with sodium citrate, that is, no methacrylate glycidyl dextran / chitosan composite solution was prepared. As can be seen from Table 1, the adsorption rates of interleukin IL-6 and bilirubin in Comparative Example 1 are significantly lower than those in Example 1 and Example 3, and the plasma protein adsorption, platelet adhesion number and plasma calcium concentration are much higher than those in Example 1 and Example 3.
[0099] From the above, it can be concluded that the adsorption capacity and anti-coagulation ability of the perfusion resin obtained by preparing a composite solution with methacrylate glycidyl dextran and chitosan and then preparing a composite hydrogel to embed the resin microparticles can be significantly improved; and when the mass ratio of methacrylate glycidyl dextran and chitosan is 1:7, the adsorption capacity and anti-coagulation ability of the perfusion resin obtained are relatively better.
[0100] Combining Example 2, Example 4-5 and Table 1, it can be seen that in the methacrylate glycidyl dextran / chitosan composite solution of Example 4-5, the total concentration of methacrylate glycidyl dextran and chitosan is different from that of Example 2. As can be seen from Table 1, the adsorption rates of interleukin IL-6 and bilirubin in Example 4-5 are lower than those in Example 2, and the plasma protein adsorption amount, platelet adhesion number and plasma calcium concentration are higher than those in Example 2.
[0101] It can be concluded from the above that in the methacrylate glycidyl dextran / chitosan composite solution, the total concentration of methacrylate glycidyl dextran and chitosan is 23wt%, and the adsorption capacity and anticoagulation ability of the prepared perfusion resin are relatively better.
[0102] Combining Example 2, Comparative Example 2 and Table 1, it can be seen that in the process of preparing the composite solution in Comparative Example 2, an equal amount of methacrylate glycidyl dextran is replaced with dextran. As can be seen from Table 1, the adsorption rates of interleukin IL-6 and bilirubin in Comparative Example 2 are much lower than those in Example 2, and the plasma protein adsorption amount, platelet adhesion number and plasma calcium concentration are significantly higher than those in Example 2. It can be seen from the above that compared with dextran, the adsorption capacity and anticoagulant ability of the perfusion resin prepared using methacrylate glycidyl dextran are relatively better.
[0103] Combining Example 2, Examples 6-7 and Table 1, it can be seen that in the grafting process of Example 6-7, the concentration of the sodium citrate solution is different from that of Example 2. As can be seen from Table 1, the adsorption rates of interleukin IL-6 and bilirubin in Examples 6-7 are lower than those in Example 2, and the plasma protein adsorption amount, platelet adhesion number and plasma calcium concentration are higher than those in Example 2.
[0104] In combination with Comparative Example 3, in Comparative Example 3, sodium citrate was not used for grafting the composite hydrogel. As can be seen from Table 1, the adsorption rates of interleukin IL-6 and bilirubin in Comparative Example 3 are much lower than those in Example 2, and the plasma protein adsorption amount, platelet adhesion number and plasma calcium concentration are much higher than those in Example 2.
[0105] From the above, it can be concluded that after the composite hydrogel is grafted with sodium citrate, the adsorption purification ability and anti-coagulation ability of the obtained perfusion resin can be significantly improved; and when the concentration of the sodium citrate solution is 4 mol / L during the grafting process, the adsorption purification ability and anti-coagulation ability of the obtained perfusion resin are relatively better.
[0106] Combining Example 2, Examples 8-9 and Table 1, it can be seen that in the grafting process of Example 8-9, the immersion time of the composite hydrogel as a whole in the sodium citrate solution is different from that of Example 2. As can be seen from Table 1, the adsorption rates of interleukin IL-6 and bilirubin in Examples 8-9 are lower than those in Example 2, and the plasma protein adsorption amount, platelet adhesion number and plasma calcium concentration are higher than those in Example 2. It can be seen from the above that in the grafting process, the composite hydrogel is immersed in the sodium citrate solution as a whole and taken out after 13 hours, and the adsorption purification ability and anticoagulation ability of the obtained perfusion resin are relatively better.
[0107] Combining Example 2, Examples 10-11 and Table 1, it can be seen that the particle size of the resin microparticles of Examples 10-11 is different from that of Example 2. From Table 1, it can be seen that the adsorption rates of interleukin IL-6 and bilirubin of Examples 10-11 are lower than those of Example 2, and the plasma protein adsorption amount, platelet adhesion number and plasma calcium concentration are higher than those of Example 2. It can be seen from the above that when the particle size of the resin microparticles is 0.05 mm, the adsorption purification ability and anticoagulation ability of the obtained perfusion resin are relatively better.
[0108] Combining Example 2, Example 12-13 and Table 1, it can be seen that in the embedding process of Example 12-13, the mass ratio of the resin microparticles and the composite hydrogel sol grafted with sodium citrate is different from that of Example 2. As can be seen from Table 1, the adsorption rates of interleukin IL-6 and bilirubin in Example 12-13 are lower than those in Example 2, and the plasma protein adsorption amount, platelet adhesion number and plasma calcium concentration are higher than those in Example 2. It can be seen from the above that when the mass ratio of the resin microparticles and the composite hydrogel sol grafted with sodium citrate is 1:6, the adsorption purification ability and anticoagulation ability of the obtained perfusion resin are relatively better.
[0109] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, all equivalent changes made according to the products, methods, and principles of the present application should be included in the protection scope of the present application.
Claims
1. A process for preparing a perfusion resin grafted with sodium citrate, characterized in that: The following steps are involved: The glycidyl methacrylate dextran and chitosan are reacted to obtain a glycidyl methacrylate dextran / chitosan composite solution, and then a composite hydrogel is obtained after cooling by injection molding; Then, the composite hydrogel is grafted with sodium citrate to obtain a composite hydrogel grafted with sodium citrate, and finally, the composite hydrogel grafted with sodium citrate is used to embed resin microparticles to obtain a perfusion resin.
2. The process for preparing a perfusion resin grafted with sodium citrate according to claim 1, characterized in that: The preparation method of the glycidyl methacrylate glycidyl dextran / chitosan composite solution comprises the following steps: Add chitosan powder into 3-4% acetic acid solution, stir for 12-14 hours at room temperature, and obtain chitosan solution after complete dissolution; Add methacrylate glycidyl dextran to the chitosan solution, stir for 12-14 hours in a 50-55° C. water bath, mix evenly and completely dissolve, then place in a 50-55° C. oven for 48-50 hours, remove bubbles, and obtain a methacrylate glycidyl dextran / chitosan composite solution, wherein the total concentration of methacrylate glycidyl dextran and chitosan is 20-25wt%.
3. The process for preparing a perfusion resin grafted with sodium citrate according to claim 2, characterized in that: In the above preparation, the mass ratio of chitosan to glycidyl methacrylate dextran is 1:(3-10).
4. The process for preparing a perfusion resin grafted with sodium citrate according to claim 1, characterized in that: The process of grafting the composite hydrogel with the sodium citrate comprises the following steps: The composite hydrogel is immersed in a sodium citrate solution as a whole, taken out after 12-14 hours, and then immersed and washed in deionized water for 2-3 days, with the water being changed every 8-10 hours, so that the hydrogel reaches a swelling equilibrium state and excess sodium citrate is removed, thereby obtaining a composite hydrogel grafted with sodium citrate.
5. The process for preparing a perfusion resin grafted with sodium citrate according to claim 4, characterized in that: In the above preparation, the concentration of the sodium citrate solution is 0.3-0.5 mol / L.
6. The process for preparing a perfusion resin grafted with sodium citrate according to claim 1, characterized in that: The resin microparticles are at least one of polymethyl methacrylate resin and polystyrene resin.
7. The process for preparing a perfusion resin grafted with sodium citrate according to claim 1, characterized in that: The particle size of the resin microparticles is 0.01-0.1 mm.
8. The process for preparing a perfusion resin grafted with sodium citrate according to claim 1, characterized in that: The embedding process comprises the following steps: The resin microparticles are weighed and poured into a composite hydrogel sol grafted with sodium citrate at a concentration of 3-5wt% and stirred evenly. The evenly mixed sol is dropped into a 2-5wt% CaCl2 solution to cross-link into spheres, and then the resin for perfusion is obtained after curing, washing and drying.
9. The process for preparing a perfusion resin grafted with sodium citrate according to claim 8, characterized in that: The mass ratio of the resin microparticles to the composite hydrogel sol grafted with sodium citrate is 1:(5-7).
10. A perfusion resin grafted with sodium citrate, characterized in that: The invention is prepared by the preparation process according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of modified bilirubin adsorbent
CN109513429A
Coating method for activated carbon adsorbent for blood perfusion
CN109621912A